2019
DOI: 10.12809/hkmj187593
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary prevention of fragility fractures: instrumental role of a fracture liaison service to tackle the risk of imminent fracture

Abstract: The occurrence of fragility fractures is strongly associated with significant morbidity and mortality. Effective recommendations should be set to treat these patients punctually for secondary prevention of fractures and ultimately decrease healthcare costs. The key pitfalls in the current management for patients with fragility fractures are the lack of fracture liaison services, low prescription rates for osteoporosis, inadequate referral for rehabilitation, and low follow-up attendance leading to poor complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…The occurrence of a fracture significantly affects clinical outcomes and healthcare costs. Ensuring the optimal exercise intervention for fracture prevention allows the potential incorporation into our Fracture Liaison Services [ 33 ]. It is important to have effective prevention of secondary fractures as the mortality is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a fracture significantly affects clinical outcomes and healthcare costs. Ensuring the optimal exercise intervention for fracture prevention allows the potential incorporation into our Fracture Liaison Services [ 33 ]. It is important to have effective prevention of secondary fractures as the mortality is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
“…The condition increases the risk of fragility fractures, which commonly occurs in the proximal femur, spine, and distal radius, leading to pain, disability, and even mortality. 6 , 7 The mainstay treatment of osteoporosis includes bisphosphonates, 8 , 9 but compliance rates are low and often lead to common side effects including gastrointestinal upset and even atypical fractures. Therefore, the development of novel diagnostics and treatments for bone loss has become a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Knee extension machines are effective to strengthen quadriceps; chair rises with weight vests or weights attached to the waist (waist belts) are an alternative to leg press machines (40). Vibration therapy provides a non-invasive, cyclic mechanical stimulation that has been shown to improve quadriceps muscle strength, balancing, and movement velocity (41). A recent study demonstrated that specific perturbation-based training program may be more efficient in preventing falls in seniors (75 years old) compared to traditional approaches (muscle strength exercises for lower extremity.…”
Section: Rehabilitation Interventions For Neurologic Elderly Patientsmentioning
confidence: 99%
“…Dynamic postural training using static and dynamic Biodex balance system had a positive effect on mobility and balance in the elderly (43). Balance training is also an important component of fall prevention for patients with fragility fractures during rehabilitation (41). Pilates exercises improved static and dynamic balance, and increase stability, mobility, flexibility and muscle strength, and decrease the fear of falling and in the number of falls in the elderly (44).…”
Section: Rehabilitation Interventions For Neurologic Elderly Patientsmentioning
confidence: 99%